2011
DOI: 10.1051/0004-6361/201015753
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the surface inhomogeneities of the contact binary SW Lacertae

Abstract: Aims. We aim to reconstruct the first detailed surface maps of the W UMa-type contact binary system, SW Lac. These maps should reveal the distributions of dark, magnetically active spot regions on the component stars and enable us to compare these with the results of similar studies of other active stars. Methods. We used the noise-reduction technique least squares deconvolution (LSD) to obtain high signal-to-noise ratio spectra of SW Lac, enabling individual starspot features to be observed in the highly rota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…But the various WD solutions converged to an overcontact situation, and there is no evidence of such a hot spot in our spectra and no significant evidence for additional third light in the system. On the other hand, a cool spot on the star that has a convective outer atmosphere is consistent with the results found for many other overcontact systems (e.g., Strassmeier 1992;Senavci et al 2011). As a result, we judged the solution with the cool spot on the secondary to be the more likely representation of the system.…”
Section: Discussionsupporting
confidence: 88%
“…But the various WD solutions converged to an overcontact situation, and there is no evidence of such a hot spot in our spectra and no significant evidence for additional third light in the system. On the other hand, a cool spot on the star that has a convective outer atmosphere is consistent with the results found for many other overcontact systems (e.g., Strassmeier 1992;Senavci et al 2011). As a result, we judged the solution with the cool spot on the secondary to be the more likely representation of the system.…”
Section: Discussionsupporting
confidence: 88%
“…Since the first study by Vogt, Penrod & Hatzes (1987) spot maps have been obtained for over 40 cool stars (see review by Strassmeier 2009). These maps have been used to understand flux emergence patterns, measure surface differential rotation rates as well as spot lifetimes and trace long-term activity cycles and trends in a range of active cool stars (e.g., Korhonen et al 1999;Barnes et al 2005;Senavci et al 2010). Zeeman Doppler Imaging (ZDI), a technique first proposed by Semel (1989), essentially applies Doppler imaging principles to circularly polarised spectra.…”
Section: Zeeman Doppler Imagingmentioning
confidence: 99%
“…Many contact binaries show signs of stellar activity, presumably because the component stars are rapid rotators with deep convective zones. Doppler imaging has revealed that some contact binaries are almost fully covered by rather irregular spot-like structures (AE Phe, Maceroni et al 1994 andBarnes et al 2004;YY Eri, Maceroni et al 1994;VW Cep, Hendry & Mochnacki 2000; SW Lac, Senavci et al 2011). Signs of high levels of coronal activity are often apparent; this helps explain why contact binaries can be relatively strong X-ray emitters (Geske et al 2006).…”
Section: Introductionmentioning
confidence: 99%